Desperate Responsibility : A Postdramatic Reading of the Author’s Presence in Shakespeare’s The Tempest - Suk, Jan (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2018)
.